مسلمان اقلیتیں اور انسانی حقوق: مغربی دنیا میں مذہبی آزادی اور قانونی چیلنجز : “Muslim Minorities and Human Rights: Religious Freedom and Legal Challenges in the Western World” (Contemporary Journal of Social Science Review, 2025)
This research examines the status of Muslim minorities in Western societies with a focus on religious freedom and legal challenges. Despite the existence of secular legal frameworks and theoretical guarantees of religious rights, Muslim communities often face social, cultural, and institutional obstacles that limit their ability to practice their faith freely. The study highlights key issues including identity crises among Muslim youth, the impact of Islamophobia, restrictions on religious symbols such as hijab or Islamic attire, and the lack of adequate representation in political and social institutions. The research further explores the tension between secular policies and religious expression, demonstrating that legal provisions alone are insufficient to ensure true equality and protection for Muslim minorities.The findings indicate that promoting legal awareness, fostering interfaith dialogue, and providing educational and cultural support are crucial for empowering Muslim communities. Islamic ethical and human rights principles are identified as a comprehensive framework that can guide both the communities and the host societies in achieving social harmony and justice. Recommendations focus on enhancing legal literacy, strengthening communal representation, addressing prejudice, and integrating Islamic perspectives on human rights into public discourse. The study emphasizes the importance of proactive measures by both Muslim organizations and host governments to create an inclusive environment that respects religious diversity.Overall, this research underscores the need for a multidimensional approach combining legal, social, and educational strategies to safeguard the rights of Muslim minorities in the Western world, promote mutual understanding, and foster peaceful coexistence.